2021
DOI: 10.1101/2021.04.02.437896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncogenic RAS activity predicts response to chemotherapy and outcome in lung adenocarcinoma

Abstract: Activating mutations in the driver oncogene KRAS occur in 32% of lung adenocarcinomas, leading to more aggressive disease and resistance to therapy in preclinical studies. However, the association between KRAS mutational status and patient outcome or response to treatment remains unclear, likely due to additional events modulating RAS pathways. To obtain a broader measure of RAS pathway activation beyond KRAS mutation only, we developed RAS84, a transcriptional signature optimised to capture RAS oncogenic acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The observation that only a narrow range signalling intensity through a signal transduction pathway is compatible with tumour development raises hopes for the therapeutic efficacy of its modulation, as recently reported for stratification of HCC response to chemotherapeutic intervention based on the inactivating Rsk2 mutations that modulate the strength of the MAPK signalling (Chan et al, 2021). Similarly, only lung adenocarcinoma with a strong Ras activating signature respond to inhibitors of the MAPK Erk pathway (East et al, 2021). It remains to be seen if the Ras pathway activation signature proves to be useful for HCC stratification for defining clinically relevant treatment options.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The observation that only a narrow range signalling intensity through a signal transduction pathway is compatible with tumour development raises hopes for the therapeutic efficacy of its modulation, as recently reported for stratification of HCC response to chemotherapeutic intervention based on the inactivating Rsk2 mutations that modulate the strength of the MAPK signalling (Chan et al, 2021). Similarly, only lung adenocarcinoma with a strong Ras activating signature respond to inhibitors of the MAPK Erk pathway (East et al, 2021). It remains to be seen if the Ras pathway activation signature proves to be useful for HCC stratification for defining clinically relevant treatment options.…”
Section: Discussionmentioning
confidence: 91%
“…Of note, whereas activating Ras mutations are rare in HCC (Zucman-Rossi et al, 2015), alterations in the intensity of MAPK Erk signalling participate in shaping the tumoral phenotype, as revealed by inactivating mutations of Rsk2, which is both an ERK target and a negative regulator of the pathway (Chan et al, 2021). Moreover, a recent analysis of transcriptional signatures classified HCC among tumours with significant Ras pathway activation phenotype (East et al, 2021). Because the same report highlighted the predictive value of strong versus weak Ras-driven transcriptional signature, it is relevant to model these phenotypes in HCC by controlled dosage of the Ras oncogene, as we have done in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to RAS mutations and prediction of MEK inhibitor sensitivity, the cell line IH1 harboring a p.G12V mutation in NRAS had the highest sensitivity to trametinib, followed by the OH2 and KJON cell lines harboring NRAS p.Q61K, and KRAS p.Q61H, respectively. The presence of RAS mutations and RAS pathway activation in lung cancer was previously shown to confer the highest sensitivity to MEK inhibitors among a panel of 500 oncology drugs ( 55 ), demonstrating that RAS mutations may be indicators of sensitivity to MEK inhibitors.…”
Section: Discussionmentioning
confidence: 97%
“…Our understanding of how the availability of extracellular stimuli, or the deregulation of their sensors, translate into cellular responses is still incomplete. For example, although only 5% of the small GTPase Ras needs to be activated to give rise to full activation of Erk ( Hallberg et al, 1994 ), a clear dosage effect has been reported in pancreatic and lung tumours for activating Ras mutations ( East et al, 2021 ; Kerr et al, 2016 ; Mueller et al, 2018 ). Moreover, amplifications of the wild-type allele of Ras that give rise to an allelic imbalance and the consequent modulation of the activity of the oncogenic Ras mutants result in distinct cellular phenotypes ( Ambrogio et al, 2018 ; Bremner and Balmain, 1990 ).…”
Section: Discussionmentioning
confidence: 99%